The The impact of Cirebon coal-fired power plants on water quality in Mundu Bay, Cirebon Regency - Millary Agung Widiawaty; Nurhanifah Nurhanifah; Arif Ismail; Moh. Dede (Center for Science and Technology, IAIN Surakarta, 2020)
The presence of Cirebon coal-fired power plant I and II caused negative effects to coastal morphology and the quality of marine waters. This also have negative impacts to the fisherman around that sea. This study aims to examine the impact of the Cirebon coal-fired power plant on the water quality of Mundu Bay, Cirebon Regency. Water quality is determined based on total suspended solids (TSS), sea surface temperatures (SST), chlorophyll-A, and salinity in the range 1999 – 2019. Data collection was carried out using satellite imagery of Landsat-5 TM, Landsat- 7 ETM+, and Landsat-8 OLI verified with in-situ field measurements, Sentinel-2 A MSI, and MODIS Aqua imageries. Changes in water quality due to the infrastructure of the two power plants are known through the Mann-Whitney U-Test and Spearman’s correlation analysis. This research shows that two Cirebon coal-fired power plant has a significant effect on changes in the quality of Mundu Bay waters. Changes in water quality are shown by a significant increase in TSS concentrations and SST values ​​accompanied by a decrease in chlorophyll-A levels and salinity levels. Changes in the quality of these waters also disrupt marine biota habitat and cause fishermen in around are difficult to get the ideal catchment yield.